Legal Protection for Neighborhood Association Administrations in the Implementation of Personal Data Collection Duties - Suwanto Putra, Steinly; Fatmawati Octarina, Nynda (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The advancement of information technology and cultural changes in information sharing have had a significant impact on how personal data is managed and accessed. The aim of this research is to determine legal protection for neighborhood administration association in the implementation of personal data collection duties. The method used by the researcher is a qualitative method with normative judicial analysis using several research questions formulated by the researcher. The Neighborhood Association (RT) requires sufficient knowledge to carry out its duties as a personal data processor as stated in the Personal Data Protection (PDP) Law. In carrying out their duties as processors, Neighborhood Association (RT) administrators must pay attention to the obligations contained in the law. However, considering the amount of data that is still being leaked, as a personal data processor, they cannot solve all the problems alone and bear the consequences as stated in the Personal Data Protection (PDP) Law. There needs to be legal certainty that also helps carry out Neighborhood Association (RT) duties as a personal data processor. Referring to countries in the world, Indonesia is lagging behind in the struggle to ensure that personal data protection laws are implemented from the private to the government level, including Neighborhood Association (RT)